THE IMPLEMENTATION OF POJK 45/2015 ON THE BANKING FINANCIAL PERFORMANCE IN INDONESIA : AN ANALYSIS - ANNA SARDIANA; ALVIEN NUR AMALIA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2018)
Otoritas Jasa Keuangan (OJK) as Financial Services Authority (FSA) in 2015, issued new regulations regarding the administration of the Remuneration Governance for Banks. With this rule, the remuneration policy applied by the Bank to Employees, Directors and Commissioners should be adjusted to follow the rules and principles set out in POJK No.45 /POJK.03/2015. Issuance of this Regulation as part of the implementation of Basel II, particularly Pillar 3 (Market Discipline), which the Bank is required to disclose information that is more transparent to the public and market participants, particularly related to remuneration to encourage discipline and allow the stakeholders to give a fair assessment. Failure to follow these rules can result in a downgrade of the factors of good corporate governance of the Bank concerned. Implementation of POJK 45 starts per 1 January 2016 for Commercial Bank Operations Group (BUKU) 3 and 4 as well as foreign banks. This study aimed to analyze the implementation of POJK 45/2015 on the financial performance of banking in Indonesia. The data which are used in this study were obtained from the Indonesian Banking Directory quarterly and look at the first kuartal of 2016 only. Samples were selected by purposive sampling method and finally obtained 27 banking companies that fulfill the criteria. Data were analyzed using financial ratios that LDR, ROA and CAR then described using qualitative description method. The results showed that the implementation of POJK 45 gives the significant positive effects on the bank performance in Indonesia.